2009
DOI: 10.1017/s1049023x00007020
|View full text |Cite
|
Sign up to set email alerts
|

Three Decades of Disasters: A Review of Disaster-Specific Literature from 1977–2009

Abstract: Introduction:The potential for disasters exists in all communities. To mitigate the potential catastrophes that confront humanity in the new millennium, an evidence-based approach to disaster management is required urgently. This study moves toward such an evidence-based approach by identifying peer-reviewed publications following a range of disasters and events over the past three decades.Methods:Peer-reviewed, event-specific literature was identified using a comprehensive search of the electronically indexed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 3 publications
0
50
0
3
Order By: Relevance
“…This paucity of SCI-specific literature reflects the broader disaster evidence base. Although a recent comprehensive review of disaster-specific literature revealed 'medical health' as the leading primary research topic following natural disasters (38%), 34 a related investigation found that 'health-care provision' and 'specific diseases' comprised only 10.2% of the topics in developing-world disaster publications. Moreover, o1% of articles retrieved addressed disasters in the developing world, where, in fact, 85% of disasters occur.…”
Section: State Of Research On Sci Rehabilitation Following Eqsmentioning
confidence: 99%
“…This paucity of SCI-specific literature reflects the broader disaster evidence base. Although a recent comprehensive review of disaster-specific literature revealed 'medical health' as the leading primary research topic following natural disasters (38%), 34 a related investigation found that 'health-care provision' and 'specific diseases' comprised only 10.2% of the topics in developing-world disaster publications. Moreover, o1% of articles retrieved addressed disasters in the developing world, where, in fact, 85% of disasters occur.…”
Section: State Of Research On Sci Rehabilitation Following Eqsmentioning
confidence: 99%
“…Although dramatic scenarios such as crush injuries and amputations grab news media attention, the basics of hygiene and water sanitation are just as critical in disaster management as is the deployment of trained response personnel into devastated areas. [127][128][129] …”
Section: Disaster Medicinementioning
confidence: 99%
“…A wide review of disaster-specific literature published from 1977 to 2009 (Smith et al 2009) showed that following 25 individual disasters or overwhelming crises, a total of 2098 peer-reviewed, event-specific publications were published in 789 journals (652 publications following disasters/events caused by natural hazards, 966 following human-made/technological disasters/events and 480 following conflict/complex humanitarian events). The event with the greatest number of peer-reviewed, event-specific publications was the 11 September 2001 terrorist attacks (686 publications).…”
mentioning
confidence: 99%
“…To mitigate the potential catastrophes that humanity is facing in the new millennium, an evidence-based approach to disaster management is urgently required (Smith et al 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation